EVALUASI BUDGETING DIVISI SATUAN PENGAMANAN PT. GREAT GIANT PINEAPPLE LAMPUNG TENGAH - Arief Pramono (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
Although the implementation of the accounting records of the budget realization in the officeof Security guards at PT. Great Giant Pineapple (GGP) has been conducted in accordance withapplicable regulations, namely the financial accounting standards. There is a risk that theimplementation of the accounting records of the realization of the budget is not appropriate or followthe applicable regulations. The method used which is the method of variable costing in theimplementation of the accounting records of the budget realization is a method of determining thecost of production which only takes into account of only the variable production costs .Realization of expenditure in the year 2011 and 2012 was in accordance with the provisionsof the financial accounting standardsand have been effective since it was based on operational costin the office of security guards at PT. Great Giant Pineapple ( GGP ). Budget variance in 2011 and2012 has been in accordance with the provisions of financial accounting standards and have beeneffective since it was based on the budget amount substracted by the amount of budget realizationthat occurred in that year.